Biological and Cellular Effects of Percutaneous Electrolysis: A Systematic Review - Jacobo Rodríguez-Sanz; Sergi Rodríguez-Rodríguez; Carlos López-de-Celis; Miguel Malo-Urriés; Soledad Pérez-Amodio; Román Pérez-Antoñanzas; Sergio Borrella-Andrés; Isabel Albarova-Corral; Miguel Ángel Mateos-Timoneda (Biomedicines)
Background: Percutaneous electrolysis is an invasive physical therapy technique that is receiving attention. The objective of this article is to evaluate the biological and cellular effects of percutaneous electrolysis and its influence on tissue healing processes. Methods. The search strategy performed in PubMed, Cochrane Library, and Web of Sciences databases resulted in a total of 25 studies. Once inclusion and exclusion criteria were applied, seven studies were finally included in this systematic review. The biological effects of percutaneous electrolysis were evaluated and grouped into pro-inflammatory and anti-inflammatory effects, cell death, and extracellular matrix and tissue remodeling effects. Results. Percutaneous electrolysis generates a significant pro-inflammatory increase in the chronic tendon condition of IL1β-6-18-1α-1rn, NLRP3, and M1 polymorphonuclear cells and increased expression of COX2, TNFα, Cxcl10, and TGFβ1 during the first 7 days. This inflammation is regulated as of day 13. A significant increase in cell death markers, such as LDH, Yo-Pro, cytochrome C, and Smac/Diablo markers, was observed during the first 7 days. Finally, a significant increase in markers Mmp9, VEGF, VEGFR, PPAR-γ/tubulin, and COL-I was observed in the extracellular matrix and tissue remodeling, and a decrease in COL-III was observed during the first 7 days. In the acute inflammatory injury condition, an increase in anti-inflammatory markers, such as IL-10-13, CCL1, and IkB, and a significant decrease in pro-inflammatory cytokines, such as IL-6-1β, CCL3-4-5, CCR5-8, NFkB, and TNFα, were observed during the first 7 days. Finally, a significant increase in VEGF, VEGFR, and PPAR-γ/tubulin markers in the extracellular matrix and tissue remodeling was observed for this condition during the first 7 days. Conclusions. Percutaneous electrolysis generates a controlled local pro-inflammatory effect in chronic conditions and regulates inflammation in inflammatory injuries (during the first 7 days). Electrolysis has short-term effects (0–7 days post) of cell death and controlled extracellular matrix destruction. Additionally, it facilitates subsequent healing by improving extracellular matrix synthesis starting from 7 days after application.